Dental Care for Patients During the Covid-19 Outbreak: A Literature Review - Monica Aponte Mendez; Ejusmar Karolina Rivera Marval; Milad Talebzade Toranji; Fatemeh Amini; Ana Regina Casaroto (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
In the wake of the rising global prevalence of the novel 2019 coronavirus disease (COVID-19), there has been much concern over infection control in patients. Due to the characteristics of the dental job, the risk of cross-infection between patients and dental personnel increases. As a result, patients who need dental intervention should consider necessary and preventive care. Therefore, the aim of the present literature review was evaluation the Dental care for patients during the covid-19. It is recommended that patients be screened by phone or video calls as much as possible and that they be questioned about the symptoms of the COVID-19 together with their latest contacts with the COVID-19 cases or hospitalized patients or even regarding their travels to the hearts of the disease. Also, if possible, it is better to examine suspected or confirmed patients with the COVID-19 in airborne infection isolation (AIIRs) or negative-pressure rooms. In conclusion, the protocols presented in this study may be of great help for delivery of dental interventions during the COVID-19 pandemic.